Ambitious Plans of the “Traffic Light” Coalition for further Vocational Training - Hartmut Seifert (Wirtschaftsdienst)
Abstract The article presents the proposals for the reorientation of vocational training listed in the coalition agreement of the new “traffic light” government and discusses them against the background of the upcoming challenges of ecological and digital structural change. However, the proposals are unrelated and do not always indicate whether they are intended to replace, supplement or expand existing programmes and approaches. For this reason, a coherent conception cannot be identified. The article shows how a sustainable concept can be formed from the approaches that are still unconnected.